Planejamento tático intermodal para a maximização do lucro no transporte e armazenagem de grãos - Vieira, Jonathan Barros Felipe (2024)
The high grain production in Brazil demands an efficient transportation system capable of delivering products at the right time and place, under acceptable conditions. However, to achieve efficiency in grain transportation, it is imperative to conduct intermodal planning. In addition to transportation, static storage is a crucial activity in grain logistics, as Brazil lacks sufficient static capacity to store the entire grain production. This necessitates an intermodal planning that integrates storage silos, transshipment terminals, and ports. Thus, considering both transportation and static capacity of grains, the research aims to propose an intermodal planning that maximizes sales profit. A literature review was conducted, focusing on identifying technical logistics factors and intermodal network structures. Based on the literature review, an intermodal graph representing the research planning was developed, incorporating the mapping of cargo transport routes and logistical decisions made by producers and cooperative managers. The next step involved developing a mathematical model that maximizes profit, considering transportation, storage costs, and grain losses, both during harvest periods and off-seasons. The model was then applied to a case study in the state of Rio Grande do Sul, covering the ten largest soy-producing cities, six warehouses, two transshipment terminals, and a port to handle approximately 1.5 million tons of grains. The case study results indicated that intermodality and grain storage provided higher profits, albeit accompanied by higher transportation and storage costs, as well as increased grain losses due to the use of road transport between intermediate nodes. Based on these results, an intermodal route for grain transport was proposed, specifying the quantity to be transported and stored in each period. Ultimately, the route proposed by the research contributes to decision-making for professionals involved in grain logistics, facilitating transport planning and promoting higher yields in grain sales.